"Belgrade to Belgradians, Not Foreign Capitalists": International Statebuilding, Contentious Politics, and New Forms of Political Representation in Serbia. Issue 1 (February 2021) - Džuverović, Nemanja; Milošević, Aleksandar
This article belongs to a forthcoming special cluster, "Contention Politics and International Statebuilding in Southeast Europe" guest-edited by Nemanja Džuverovic, Julia Rone and Tom Junes . One of the main criticisms concerning the process of post-conflict transition in Serbia has been the lack of context sensitivity and participation of the local population in the decision-making process, especially regarding the most important issues that were addressed during the political and economic transformation of the country that began in 2001. This criticism became especially pronounced from the beginning of the economic crisis in 2008, when the negative characteristics of international statebuilding became even more apparent, causing increased dependency on international institutions and further economic marginalisation of the most vulnerable groups. By looking at the movement "Don't Drown Belgrade" and the series of large-scale protests in Belgrade in 2016, the article seeks to explore the main reasons for social discontent with the international-led statebuilding agenda in post-conflict Serbian society and the local strategies employed to resist and subvert this form of statebuilding.